Apoptotic signal molecules in skin biopsies of cutaneous lupus erythematosus: analysis using tissue microarray - Toberer, Ferdinand; Sykora, Jaromir; Göttel, Daniel; Hartschuh, Wolfgang; Werchau, Siegfried Arthur; Enk, Alexander; Joos, Stefan; Krammer, Peter H.; Kuhn, Annegret (Experimental dermatology, 2013)
Cutaneous lupus erythematosus (CLE) is a heterogeneous autoimmune disease. Different pathogenetic mechanisms, including the accumulation of apoptotic keratinocytes in CLE, have been reported. Therefore, we investigated whether CLE and other inflammatory skin diseases differ with regard to the epidermal expression of molecules that are crucial for the initiation and regulation of apoptosis. In this study, 241 skin biopsies from patients with CLE, psoriasis (PSO), lichen planus (LP) and healthy controls (HCs) were analysed immunohistochemically using the tissue microarray (TMA) technique. The TUNEL assay and anti-activated caspase-3 antibodies revealed a significant increase of apoptotic keratinocytes in CLE lesions compared with HCs. Furthermore, we detected a significant increase in the epidermal expression of CD95 in CLE specimens compared with PSO, LP and HCs. These data suggest that the accumulation of apoptotic keratinocytes in CLE might be due to the increased epidermal expression of CD95, resulting in increased activity of the extrinsic apoptotic pathway in the disease.
Gesehen am 07.02.2022